Targeted Metabolic Engineering of Saccharomyces cerevisiae for High-Efficiency Valorization of Lignocellulosic Biomass into Superior-Quality Bioplastics - Nur Diana; Zaki Ahmad; Selma Fajic (Natural Sciences Engineering and Technology Journal, 2025)
The global transition towards a sustainable circular bioeconomy urgently requires innovative platforms for converting renewable waste streams into value-added products. Lignocellulosic biomass, particularly agricultural residue like rice straw, stands as a vast, underutilized carbon source. This study details the systematic metabolic engineering of Saccharomyces cerevisiae for the high-efficiency production of poly(3-hydroxybutyrate) (PHB), a biodegradable bioplastic, from rice straw hydrolysate. A multi-faceted synthetic biology approach was implemented in S. cerevisiae CEN.PK2-1C. A robust xylose co-utilization pathway was integrated using codon-optimized genes from Scheffersomyces stipitis. The PHB biosynthesis pathway from Cupriavidus necator was introduced using a cassette of strong, constitutive yeast promoters (pTDH3, pTEF1, pPGK1). To maximize carbon flux towards PHB, key competing pathways were eliminated via CRISPR-Cas9-mediated gene knockouts of the primary alcohol dehydrogenase (ADH1) and glycerol-3-phosphate dehydrogenase (GPD1) genes. The performance of the final engineered strain was evaluated in high-cell-density fed-batch fermentation using detoxified rice straw hydrolysate sourced from Palembang, Indonesia. The final engineered strain, YL-PHB-05 (Δadh1 Δgpd1), demonstrated superior performance. In fed-batch bioreactor cultivation, it achieved a final cell dry weight of 33.8 ± 1.5 g/L and a PHB titer of 15.2 ± 0.7 g/L, with an intracellular PHB accumulation of 45.0 ± 1.2% of cell dry weight. This corresponds to a high yield of 0.28 g PHB per gram of consumed sugars. Crucially, the produced PHB exhibited a superior weight-average molecular weight (Mw) of 1.2 x 10⁶ Da with a polydispersity index of 2.1. In conclusion, this work successfully demonstrates a robust strategy for engineering S. cerevisiae into an efficient cell factory for producing high-quality bioplastics from a globally relevant agricultural waste stream. The high titers, yields, and superior polymer properties achieved present a significant advancement towards establishing an economically viable and sustainable process for bioplastic production within a circular bioeconomy.